Integrating Multi-Criteria Decision Analysis in Healthcare Policy and Practice - Emmanouil-Kalos, Alkinoos (HAPSc Policy Briefs Series, 2024)
Decision-making in healthcare financing requires balancing diverse and often competing criteria. Multi-Criteria Decision Analysis (MCDA) offers a structured framework for evaluating multiple factors simultaneously, enhancing efficiency, transparency and consistency. This policy brief explores the integration of MCDA in healthcare, detailing its advantages in supporting comprehensive evaluations and succinctly presenting various prominent MCDA models. Moreover, a step-by-step framework for applying MCDA in healthcare decision making is presented, emphasizing stakeholder engagement and criterion selection. Finally, the brief addresses the challenges that accompany MCDA implementation and offers strategies to mitigate these issues.